2020
DOI: 10.2147/ijwh.s272867
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exploration of Lifestyle Choices, Reproductive Health Knowledge, and Polycystic Ovary Syndrome (PCOS) Awareness Among Female Emirati University Students</p>

Abstract: Objective Healthy lifestyle and adequate reproductive health knowledge are prerequisites for maintenance of physical and mental well-being of women across the world. With increasing prevalence of metabolic disorders such as polycystic ovary syndrome (PCOS), it is important that sufficient awareness of these issues is generated, especially in conservative communities in Arab regions. The main objective of this study is to assess reproductive health (RH) knowledge and awareness of PCOS among female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 37 publications
1
25
2
1
Order By: Relevance
“…On the other hand, there was no significance in a family history of DM and obesity, which were different from studies established in Greeks, United Arab Emirates, and Libya (71%, 75.5%,82%) respectively 21,22 . Furthermore, in current study, smoking did not affect androgens (TT and DHEA-S) (p<0.45, p<0.72) among PCOs women.…”
Section: Resultscontrasting
confidence: 98%
“…On the other hand, there was no significance in a family history of DM and obesity, which were different from studies established in Greeks, United Arab Emirates, and Libya (71%, 75.5%,82%) respectively 21,22 . Furthermore, in current study, smoking did not affect androgens (TT and DHEA-S) (p<0.45, p<0.72) among PCOs women.…”
Section: Resultscontrasting
confidence: 98%
“…Youth were often not able to self-advocate compared to older participants, who emphasized the need for self-advocation at the doctor’s office. Several studies found little awareness of PCOS in students internationally [ 49 , 50 ] and a need for awareness programmes [ 51 , 52 ]; however, more research is needed to gauge awareness levels in adolescents in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Females with PCOS have increased risk of type 2 diabetes, metabolic syndrome, and cardiovascular diseases (CVDs). 2 4 There is a four to seven times more risk of heart attack in females diagnosed with PCOS than females who do not have PCOS in the same age group. 2 Psychological features include loss of femininity, body dissatisfaction, anxiety, depression, eating disorders, and suicidal attempts which are more prevalent in PCOS population.…”
Section: Introductionmentioning
confidence: 99%